Citizen journalism in action: empowering the rural community via citizen journalism - Mahamed, Mastura; Omar, Siti Zobidah; Tamam, Ezhar; Krauss, Steven Eric (Human Resource Management Academic Research Society, 2018)
Citizens including in rural areas have adopted the internet to create alternative space for multiple viewpoints. In many occasions, rural development received limited coverage from the mainstream media. The issue limited access to mainstream media has force rural communities seek alternative platforms showcasing rural communities and development. The information and communication technology (ICT) and digitalization innovation is providing more platforms and empower people opportunity to voice out and engage actions to issues that they felt worth advocating for and long been neglected by the mainstream media by utilizing mew media platforms including among rural communities and their sustainability. Citizen journalism is making an attempt to address this problem by enabling rural communities to obtain and report news, and, to facilitate coverage of their concerns and interest, by connecting those communities and a virtual news outlets prospects to ensure their voice is also heard to initiate actions and mobilization towards a more sustainable rural community. The purpose of this paper is to analyse to what extent citizen journalism does could be a platform to empower community by exercising freedom of expression by producing hyperlocal stories discussing local issues and interest. Based on analysing previous literatures, findings suggest rural communities around the world choose to join the growing number of citizen journalists. It is interesting to see if the primary contribution of citizen journalism potential to empower rural communities.